Фразеологізми з семантикою інтенсивності як об’єкт наукового дослідження - Дідун, Л. (Лексикографічний бюлетень, 2011)
Article focuses on the semantics of phraseological units of intensity in modern
Ukrainian literary language. The attention is drawn to semantic aspects of studying
phraseology. We consider the expressiveness as a special component of the semantic
structure of phraseology. The measure expression of the expressive phraseology in
speaking intensity. Linguists consider the intensity as a semantic category. Category
of intensity is based on the consideration of the semantics of phraseology as complete
units. Phraseologisms semantics of intensity designed to make the expression more
convincing for the perception of the recipient.